Incidence of pressure ulcer in patients using an alternating pressure mattress overlay: the ACTIVE study. (2nd February 2021) - Meaume, Sylvie; Rousseaux, Chantal; Marty, Marc
Abstract : Objective: The primary objective was to determine the clinical benefit of using a specific alternating-pressure mattress overlay (APMO) in the prevention of pressure ulcer (PU) in patients at medium to high risk. Method: This prospective study was conducted in five rehabilitation centres and three nursing homes. Patients at medium to high risk of PU, but without PU at baseline, and lying between 15 and 20 hours per day on a specific APMO were included. The primary endpoint was the percentage of patients who developed a sacral, spine, heel or trochanteric PU (supine support areas) of at least category II, at day 35. All patients were included in the analysis. Results: A total of 89 patients were included; of whom six patients (6.7%) dropped out of the study (average (±standard deviation) follow-up 32±5.4 days). No sacral, spine, heel or trochanteric PU of at least category II was reported (i.e., an incidence of 0% [95% Confidence Interval: 0–4.1%] according to the exact Clopper–Pearson method]. Patients were 'satisfied' or 'very satisfied' with the comfort and stability of the APMO. The caregivers assessed as 'very easy' or 'easy' the implementation, maintenance and use of the APMO (turning over, moving to a sitting position). Conclusion: In combination with the usual measures to prevent PU, the results of our study showed a low incidence of PU in high-risk patients lying for between 15 and 20 hours a day on an APMO, use of which is therefore recommended in these patients.